P-029 Use of the Sceptre C Dual-Lumen Balloon Microcatheter in Onyx Embolization of Cerebral Arteriovenous Malformations: A Multi-Center Experience. (26th July 2014) - Spiotta, A; James, R; Lowe, S; Janjua, R; Delay, J; Quintero-Wolfe, S; Turk, A; Chaudry, M; Turner, R
Abstract : Introduction: Conventional onyx embolization of cerebral arteriovenous malformations (AVMs) requires lengthy procedure and fluoroscopy times to form an adequate 'proximal plug' for distal delivery of the material while minimising the likelihood of reflux and nontargeted embolization. We review our experience with balloon-augmented onyx embolization of AVMs utilising a dual-lumen catheter. Methods: Data was obtained retrospectively from three centers (Medical University of South Carolina, East Carolina University, Wake Forest). Utilising a 0.014 inch microwire a Sceptre C balloon catheter (MicroVention) was advanced into the arterial pedicle of interest and Onyx embolization was carried out after balloon inflation. Results: Seventeen patients were treated (age 43 ± 21 yr) and a total of 34 arterial pedicles were embolised with the Sceptre C catheter over twenty one discreet treatment episodes. The mean number of pedicles embolised per patient was 2 (range 1 to 5) and AVMs were treated in a wide variety of intracranial locations (size 3.55 ± 1.61 cm). In all cases the Sceptre C catheter was navigated into the desired position. Fluoroscopy time for the entire procedure was 48 ± 26 min (mean fluoroscopy time per arterial pedicle embolised was 28 min). Immediate angiographic outcomes: complete occlusion (n = 2), 90–99% reduction in nidus (n = 5), 70–89% reduction (n = 6), 50–70% (n = 4), 25–49% reduction (n = 3) and <25% reduction (n = 1). Two catheter related complications (11%) were observed; an intraprocedural rupture of a feeding pedicle and a retained catheter fragment within the onyx cast. Conclusion: In our experience, balloon-augmented onyx embolization utilising a dual lumen catheter is safe and effective in the treatment of AVMs, allowing more efficient and controlled injection of Onyx with a decreased risk of reflux and drastically decreased fluoroscopy times. Disclosures: A. Spiotta: 1; C; Stryker, Microvention, Penumbra. 2; C; Stryker, Microvention, Penumbra. 3; C; Stryker, Microvention, Penumbra. R. James: None. S. Lowe: None. R. Janjua: None. J. Delay: None. S. Quintero-Wolfe: None. A. Turk: 1; C; Stryker, Microvention, Penumbra. 2; C; Stryker, Microvention, Penumbra. 3; C; Stryker, Microvention, Penumbra. M. Chaudry: 1; C; Stryker, Microvention, Penumbra. 2; C; Stryker, Microvention, Penumbra. 3; C; Stryker, Microvention, Penumbra. R. Turner, IV: 1; C; Stryker, Microvention, Penumbra. 2; C; Stryker, Microvention, Penumbra. 3; C; Stryker, Microvention, Penumbra.